Children's wellness: outdoor learning during Covid-19 in Canada - Anna Burke; Sylvia Moore; Laura Molyneux; Ayla Lawlor; Terri Kottwitz; Ginny Yurich; Renee Sanson; Ola Andersen; Breanne Card (University of Aberdeen, School of Education, 2021)
Outdoor learning has been a topic of recent discussion due to the Covid-19 global pandemic, which led to the closure of many schools, daycares, and regular programming, and the negative repercussions that affect children. Here, we consider the changing practices related to outdoor learning and Indigenous land-based learning during the pandemic, and the implications for children's wellbeing, development and learning. Indigenous culture, relating to traditional learning and knowledge, and cultural connections to the land, is also considered to interrogate how outdoor, nature-based, and on the land experiences affect community wellness. This paper draws on interviews with the leaders of two forest schools, Cloudberry Forest School and ForestKids, and the creator of the 1000 Hours Outside Program. Common themes, such as 'nature as the teacher' (trust regulation), environmental stewardship, social cohesion, physical and mental well-being, and Indigenous' ways of knowing were identified across the interviews. This study reveals practical implications for teachers regarding the importance of access to nature based free play children's development, and the importance of land- based education for Indigenous children.